2009
DOI: 10.1002/art.25001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of DNA binding/differentiation 2 induced by hypoxia promotes synovial fibroblast–dependent osteoclastogenesis

Abstract: Objective. To map hypoxic areas in arthritic synovium and to establish the relevance of low oxygen levels to the phenotype of synovial fibroblasts, with special focus on bone degradation.Methods. To analyze the distribution of hypoxia in arthritic joints, the hypoxia marker EF5 was administered to mice with collagen-induced arthritis (CIA). To evaluate the effect of hypoxia on rheumatoid arthritis synovial fibroblasts (RASFs), reverse suppression subtractive hybridization and complementary DNA array were used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Id2, inhibitor of DNA binding 2 (42), a transcriptional regulator containing a helix-loop-helix (HLH) domain but not a basic domain, inhibits the functions of basic HLH transcription factors in a dominant-negative manner by suppressing their heterodimerizing partners through the HLH domain. We next examined Id2 downstream genes such as M-CSF and collagen 1a1 genes in Set-R cells, which were previously shown to be positively regulated by Id2 (43,44), and clearly found their expressions markedly augmented in Set-R cells (Fig. 4B).…”
Section: Suppression Of Id2 Expression By Setdb1mentioning
confidence: 85%
“…Id2, inhibitor of DNA binding 2 (42), a transcriptional regulator containing a helix-loop-helix (HLH) domain but not a basic domain, inhibits the functions of basic HLH transcription factors in a dominant-negative manner by suppressing their heterodimerizing partners through the HLH domain. We next examined Id2 downstream genes such as M-CSF and collagen 1a1 genes in Set-R cells, which were previously shown to be positively regulated by Id2 (43,44), and clearly found their expressions markedly augmented in Set-R cells (Fig. 4B).…”
Section: Suppression Of Id2 Expression By Setdb1mentioning
confidence: 85%
“…Thus, the role of Ids seems to be more complex in vivo . Hypoxia-induced Id2 expression is found in rheumatoid arthritis synovial fibroblasts, and promotes synovial fibroblast-dependent osteoclastogenesis [61]. Another study showed that overexpression of Id1 in prostate cancer cells has an important role in promoting prostate cancer-mediated osteoclast differentiation, probably via certain secreted factors [62].…”
Section: Transcriptional Repressors: Ids Eos Mafb C/ebpβ Irf-8 Bcl6mentioning
confidence: 99%
“…The current study has shown that conditioned medium of osteoclastlike cells can influence the adhesion molecule pathway of fibroblasts. Hypoxia-induced ID-2 may contribute to joint destruction in RA patients by promoting synovial fibroblast-dependent osteoclastogenesis (10). Moreover, oestrogen can inhibit osteoclast formation induced by periodontal ligament fibroblasts (11).…”
Section: Mirna Microarray Data Analysismentioning
confidence: 99%